2019
DOI: 10.1002/jcp.28755
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐455‐5p ameliorates HG‐induced apoptosis, oxidative stress and inflammatory via targeting SOCS3 in retinal pigment epithelial cells

Abstract: Diabetic retinopathy (DR) remains the leading cause of blindness in adults with diabetes mellitus. Numerous microRNAs (miRNAs) have been identified to modulate the pathogenesis of DR. The main purpose of this study was to evaluate the potential roles of miR-455-5p in high glucose (HG)-treated retinal pigment epithelial (RPE) cells and underlying mechanisms. Our present investigation discovered that the expression of miR-455-5p was apparently downregulated in ARPE-19 cells stimulated with HG. In addition, force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 28 publications
0
23
1
Order By: Relevance
“…CRT change may also implicate the morphological disruption and dysfunction of the inner or outer blood-retinal barrier during the development of disease. [54][55][56][57][58] There was no significant difference between pegaptanib every 6 weeks and the sham injection group in terms of efficacy and safety, which differs from the results of the VISION trials. 17,59 This finding, together with National Institute for Health and Care Excellence (NICE) guidance, indicated that pegaptanib is not recommended for the treatment of nAMD.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…CRT change may also implicate the morphological disruption and dysfunction of the inner or outer blood-retinal barrier during the development of disease. [54][55][56][57][58] There was no significant difference between pegaptanib every 6 weeks and the sham injection group in terms of efficacy and safety, which differs from the results of the VISION trials. 17,59 This finding, together with National Institute for Health and Care Excellence (NICE) guidance, indicated that pegaptanib is not recommended for the treatment of nAMD.…”
Section: Discussioncontrasting
confidence: 70%
“…CRT change may also implicate the morphological disruption and dysfunction of the inner or outer blood-retinal barrier during the development of disease. 54 58 …”
Section: Discussionmentioning
confidence: 99%
“…Considering retinal pigment epithelial (RPE) cells, miR-455-5p ameliorated OxS and inflammation triggered by HG, as shown by the increased activity of antioxidant defense genes (SOD, CAT, GPx), reduced ROS production, expression of NOX4 and proinflammatory cytokines. This beneficial impact was proven to be mediated by the direct regulation of previously mentioned SOCS3 [255]. In another study, quercetin elicited the upregulation of miR-29b in HG-exposed RPE cells, thus leading to amelioration of ROS production due to miR-29b-dependent beneficial regulation of PTEN/AKT and NF-κ pathways [256].…”
Section: Mirnas In Mets-a Link With Obesity and Insulin Resistance/hymentioning
confidence: 90%
“…Suppressor of cytokine signaling 3 (SOCS3) is a direct target gene of miR-455-5p and negatively regulated by miR-455-5p. The study showed that augmentation of miR-455-5p remarkably alleviated HG-triggered oxidative stress injury as reflected by decreased the production of intracellular ROS and malondialdehyde (MDA) content as well as NADPH oxidase 4 expression, concomitant with enhanced the activities of superoxide dismutase, catalase, and GPX [48]. That is to say, miR-455-5p has antioxidant activity and could be as a new potential therapeutic agent for DR treatment.…”
Section: Mir-365 and Mir-455-5pmentioning
confidence: 93%